Mandatul aleșilor locali - mandat de drept public. Consecințe juridice - Camelia Florentina STOICA (Revista Transilvană de Ştiinţe Administrative, 2011)
The article presents the legal regime in public law applicable to the mandate of the local representatives. Unlike the private law mandate, the public law mandate is not defined in any normative act, does not have a detailed regulation, his juridical nature and characteristics being established by the doctrine, starting from the common fundament of the public and private law mandate, which is of the essence of the mandate. The interdiction of the imperative mandate is in fact a means of protection of the freedom and independence of the members of the Parliament. On the political side, the disregard of the commitments of the elected person towards the political party may have as a consequence the expulsion from the party. In the second part of the article the arguments for a unitary regime of the national and local public law mandate are presented. In addition to that proposals have been made, on one side for reconsidering the case law of the Constitutional Court with respect to the public law mandate and the modification of Law no. 393/2004 concerning the local representatives, and on the other side, in accordance with the constitutional provisions which forbid the interactive mandate.